Psychological Manifestations of Intrapersonal Conflicts in Professional Activities of Nurses - Pavlyuk, T. (Psychological Prospects Journal, 2013)
An attempt to study empirically the intrapersonal conflicts of nurses as miscoodination of desirability and availability of professional values realization was made in the article. The specificity of their manifestations in nurses with a different level of emotional burnout was revealed.
Keywords: intrapersonal conflict, values of professional activity, value motivated miscoodination, emotional burnout.